Design and implementation of an IoT multi-interface gateway for establishing a digital art interactive system. (2016) - Bai, Zhi-yong; Kuo, Chin-Hwa; Wang, Tzu-Chia
The internet of things (IoTs) can be established by connecting smart objects in a wireless manner. However, a variety of wireless technologies, including Bluetooth, ZigBee, WiFi and infrared, which have been embedded into smart objects or controllers, cannot exchange information since they apply different standards or even work on different frequencies. To provide information exchange in heterogeneous networks, this paper proposes the design and implementation of an IoT multi-interface gateway, which can transform the information into a data which can be recognised by various smart objects. In the implementation, the IoT multi-interface gateway can be used for digital arts or some smart spaces that can automatically control traditional TV, air condition, smart meter, sphygmomanometer, smart phone, etc. The implementation shows that the IoT gateway can exchange data among various smart objects that use different wireless technologies and also guarantee the stability of data conversion time.